The Development of Digital Comic Media for Science Subject to Improve Information Technology Literacy Skill for Grade IV Elementary School Students - Ledi Merlin Purwati; Bambang Subali; Saiful Ridlo (Journal of Primary Education, 2022)
The aim of this study is to determine the effect of implementing the results of digital comic development in improving the information technology literacy skill of fourth grade elementary school students. This study used RnD method with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The research subject was fourth grade students at Kuranji State Elementary School, Cirebon City. Furthermore, the data collection technique was the media expert, linguist, material expert validation questionnaire, test techniques and student responses. Aiken's validity results show the lowest index results from media experts, language experts and material experts of 0.67 and the highest index is 1. Furthermore, the results show that the student test instrument variables are declared reliable based on Cronbach's Alpha reliability calculations that is 0.937 with very high criteria. The Pearson Product Moment correlation coefficient value between the implementation of digital comic development results and students' information technology literacy skills is 0.693. Digital comics affect students' technological literacy skills 48.0%. Moreover, the average percentage of student responses to the implementation of digital comic development in energy sources science learning materials for class IV elementary schools is 94.4% with very high criteria. Digital comic media is feasible, and it has a significant effect on increasing the information technology literacy skills of fourth grade elementary school students.